FLOWABILITY OF DUSTS FROM DRY OFF-GAS CLEANING: THE INFLUENCE OF PARTICLE SIZE AND THE SPREAD OF THE SIZE DISTRIBUTION - Lanzerstorfer, Christof (MATTER: International Journal of Science and Technology, 2017)
Considerable amounts of fine granular dust result from dry off-gas cleaning systems. The flowability of these dust is an important characteristic for the design of dust-conveying and storage equipment. In this study, the relationship between the flow-relevant properties unconfined yield strength and flowability and important properties of the dust (Sauter mean diameter, the spread of the size distribution) were investigated based on the data of seventy specks of dust from dry off-gas cleaning systems. The results showed that the Sauter mean diameter of a dust from dry off-gas cleaning can be used as the basis for a rough estimate of the unconfined yield strength and the flowability. As is well-known, for coarser dust the unconfined yield strength is typically lower and the flowability is higher. The influence of the spread of the size distribution is comparatively low. However, to obtain reliable flowability data shear tests are obligatory.